'Smart' light‐reflective windows based on temperature responsive twisted nematic liquid crystal polymers. Issue 12 (22nd February 2021) - Kragt, Augustinus J. J.; Loonen, Roel C. G. M.; Broer, Dirk J.; Debije, Michael G.; Schenning, Albert P. H. J.
Abstract: 'Smart' windows which reversibly increase their reflectivity upon heating are attracting considerable attention as devices for maintaining comfortable indoor environmental conditions. In this work, twisted nematic semi‐interpenetrating liquid crystal networks which lose their order upon heating are sandwiched between reflective linear polarizers. This 'smart' window reversibly decreases its transmission from about 50–10% over a wavelength range between 400 and 1100 nm upon heating, resulting in the window becoming darker and reflecting more light. This 'smart' window is potentially interesting for energy saving window applications where variation between privacy and visible light transparency states is required. Abstract : In this work, twisted nematic semi‐interpenetrating liquid crystal networks which lose their order upon heating are sandwiched between reflective linear polarizers. This 'smart' window is potentially interesting for energy‐saving window applications where variation between privacy and visible light transparency states is required.